THE HUBUNGAN TINGKAT PENGETAHUAN GIZI SEIMBANG PADA IBU BALITA 12–59 BULAN DENGAN KEJADIAN STUNTING DI WILAYAH KERJA UPTD PUSKESMAS CIBINGBIN KABUPATEN KUNINGAN TAHUN 2025: HUBUNGAN TINGKAT PENGETAHUAN IBU BALITA STUNTING DI WILAYAH KESENJANGAN KESEJAHTERAAN - Yuliani, Artitha Inayah; Prayuda, Cahyani Wira; Nur'Aisah, Enung (Poltekkes Kemenkes Kendari, 2025)
The prevalence of stunting in Cibingbin District has reached 8.9%, partly due to low family welfare levels, which serve as a major risk factor in fulfilling children's nutritional needs. This study aims to determine the relationship between mothers' level of knowledge about balanced nutrition and the incidence of stunting among children aged 12–59 months in the working area of UPTD Puskesmas Cibingbin, Kuningan Regency, particularly in the villages of Sukaharja, Ciangir, Cipondok, and Sindangjawa. The study employed a quantitative approach with a cross-sectional design to assess the relationship between variables at a single point in time. A total of 64 respondents were selected using the cluster random sampling technique. Data collection instruments included a closed-ended questionnaire to measure mothers' knowledge of balanced nutrition and anthropometric measurements using height-for-age (TB/U) indicators to determine stunting status. The results showed that most mothers had low knowledge of balanced nutrition (75%). Among the children, 45.3% were categorized as stunted and 54.7% as severely stunted. Statistical analysis using the Spearman Rank test revealed a significant relationship between mothers' knowledge of balanced nutrition and stunting incidence (p = 0.032; r = -0.268), with a negative correlation.